Making it work - fitting parenthood into an elite sport career - Hellborg, A. M. (Sport in Society: Cultures, Commerce, Media, Politics, 2023)
The purpose of this study is to analyze and problematize the possibilities and challenges of combining an elite sport career with parenthood among elite athletes in Sweden. Specific focus will be on time management, financial conditions, and support. Ten active or formerly active elite athletes who had combined or tried to combine elite sports with parenthood were interviewed. The athletes represent a range of different sports and played in teams or as individual competitors. Some were full-time athletes, while others had additional employment. Work-family conflict was present for the athletes, with the results showing that combining elite sports with parenthood can work, but only if the athlete has adequate resources. The most important resource is social support from the athlete`s family. The sport organizations appear somewhat invisible as a supportive structure; therefore, the athletes have contributed with ideas of what these organizations can do to increase their support.